A sexually dimorphic distribution of corticotropin-releasing factor receptor 1 in the paraventricular hypothalamus - Rosinger, Zachary J (Neuroscience, 2019)
Sex differences in neural structures are generally believed to underlie sex differences reported in anxiety, depression, and the hypothalamic-pituitary-adrenal axis, although the specific circuitry involved is largely unclear. Using a corticotropin-releasing factor receptor 1 (CRFR1) reporter line, we report a sexually dimorphic distribution of CRFR1 expressing cells within the paraventricular hypothalamus (PVN; males > females). Relative to adult levels, PVN CRFR1-expressing cells are sparse and not sexually dimorphic at postnatal days 0, 4, or 21. This suggests that PVN cells might recruit CRFR1 during puberty or early adulthood in a sex-specific manner. The adult sex difference in PVN CRFR1 persists in old mice (20–24 months). Adult gonadectomy (6 weeks) resulted in a significant decrease in CRFRI-immunoreactive cells in the male but not female PVN. CRFR1 cells show moderate co-expression with estrogen receptor alpha (ERα) and high co-expression with androgen receptor, indicating potential mechanisms through which circulating gonadal hormones might regulate CRFR1 expression and function. Finally, we demonstrate that a psychological stressor, restraint stress, induces a sexually dimorphic pattern of neural activation in PVN CRFR1 cells (males >females) as assessed by co-localization with the transcription/neural activation marker phosphorylated CREB. Given the known role of CRFR1 in regulating stress-associated behaviors and hormonal responses, this CRFR1 PVN sex difference might contribute to sex differences in these functions.